Physiology of digestive and excretory systems. Physiology of sensory systems and higher nervous activity laboratory workbook - Evstafyeva E. (Симферополь, КФУ им. В.И. Вернадского, 2024)
Normal physiology. Laboratory workbook offers an enjoyable and highly effective way to revise human physiology. Designed for medical students as a companion to the textbook and practical classes. Complete the corresponding sections of the Workbook as you proceed from topic to topic in class learning body systems. Chapter by chapter, practical tasks, fill in the blanks, short answer quizzes, multiple choice questions and other activities promote understanding of the essentials of physiology.